2006
DOI: 10.1159/000094126
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Is Associated with VCAM-1 Dependent Adhesion of Gastric Cancer Cells to Endothelial Cells

Abstract: Background/Aims: Cell adhesion molecules play a critical role in the invasion and metastasis of a variety of human tumors. Abnormal expression of VCAM-1 has been demonstrated to correlate with the malignant progression of gastric tumors, but the molecular mechanism underlying the VCAM-1-dependent metastasis has been rarely investigated. To explore the role for tumor cell-expressing adhesion molecules in the carcinoma-endothelium adhesion, we analyzed expression status of adhesion molecules in gastric cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…It is interesting that K-Ras-mutated cell lines showed an elevated expression of caveolin-1 (Supplementary Figure S5d). Thus, we eliminated caveolin-1 through si-RNA (Shin et al, 2006) and measured p53 endocytosis. Si-caveolin-1 could block p53 endocytosis in A549 (Supplementary Figure S5e).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that K-Ras-mutated cell lines showed an elevated expression of caveolin-1 (Supplementary Figure S5d). Thus, we eliminated caveolin-1 through si-RNA (Shin et al, 2006) and measured p53 endocytosis. Si-caveolin-1 could block p53 endocytosis in A549 (Supplementary Figure S5e).…”
Section: Resultsmentioning
confidence: 99%
“…Primers were designed where possible to span intron/exon borders and specificity was checked using the European Molecular Biology Laboratory (EMBL)-GenBank database software using the BLAST program. The respective Forward and Reverse primers were: Targeted (siRNA) down-regulation of caveolin-1 and tamoxifen sensitivity assays As previously described [32,33] a siRNA duplex (21 nucleotides) targeting the caveolin-1 mRNA sequence 5 0 -AACCAGAAGGGACACACAGUU-3 0 was used to downregulate caveolin-1 protein expression and a siRNA duplex targeting the firefly luciferase (GL2) mRNA sequence 5 0 -AACGUACGCGGAAUACUUCGA-3 0 was used as a negative control. The duplexes were purchased from MWG (Ebersberg, Germany) as unprotected, desalted, and purified siRNA.…”
Section: Rt-pcrmentioning
confidence: 99%
“…It is also thought that enhanced Cav-2 expression alters signal transduction in UC, thus indicating a role for caveolae in IBD (5). Cav-1 is associated with VCAM-1 in progression of tumor vasculature and is necessary for remodeling the vasculature (138,167). Additionally, Sonveaux et al (142) showed that Cav1 Ϫ/Ϫ mouse cells exhibit poor tube formation in cultured endothelium (32).…”
Section: Angiogenic Mediators In Ibd and Experimental Colitismentioning
confidence: 99%